2016
DOI: 10.1155/2016/5156295
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Acromegaly Presenting with Colon Cancer: A Case Series

Abstract: Introduction. Frequent colonoscopy screenings are critical for early diagnosis of colon cancer in patients with acromegaly. Case Presentations. We performed a retrospective analysis of the incidental diagnoses of colon cancer from the ACCESS trial (ClinicalTrials.gov identifier: NCT01995734). Colon cancer was identified in 2 patients (4.5%). Case  1 patient was a 36-year-old male with acromegaly who underwent transsphenoidal surgery to remove the pituitary adenoma. After surgery, the patient underwent routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In some studies, colon polyps and/or cancer have been reported to occur more frequently in acromegaly than in the general population, although data from other studies have not supported this association [ 49 , 50 ]. There is general agreement, however, that early colonoscopy screening and regular surveillance is justified [ 38 , 49 , 51 54 ]. The Screening Guidelines for Colorectal Cancer and Polyps in Acromegaly [ 52 ] recommend regular colonoscopic screening, starting at 40 years of age, with frequency of repeat colonoscopy depending on findings at original screening and acromegaly activity.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, colon polyps and/or cancer have been reported to occur more frequently in acromegaly than in the general population, although data from other studies have not supported this association [ 49 , 50 ]. There is general agreement, however, that early colonoscopy screening and regular surveillance is justified [ 38 , 49 , 51 54 ]. The Screening Guidelines for Colorectal Cancer and Polyps in Acromegaly [ 52 ] recommend regular colonoscopic screening, starting at 40 years of age, with frequency of repeat colonoscopy depending on findings at original screening and acromegaly activity.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of colorectal cancer is a complex process that involves multiple factors. As the early clinical symptoms of colon cancer patients are not obvious, most patients are diagnosed at the advanced stage of colon cancer ( 10 ). The epigenetic changes also play a very important role in the incidence and development of colon cancer ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is a malignant tumor with relatively higher incidence, and the incidence is on the increase annually in China due to the change in eating habits ( 11 ). Due to the absence of any obvious early clinical symptoms, many patients with colon cancer are usually diagnosed when the disease is already in late-stage and is already too late for surgical intervention ( 12 ).…”
Section: Discussionmentioning
confidence: 99%